Apoptosis inhibitor of macrophage suppress immune responses via IL-10 production and delay bacterial clearance in Mycobacterium avium infection - Kajiwara, Chiaki; Shiozawa, Ayako; Arai, Satoko; Yamaguchi, Tetsuo; Harada, Sohei; Miyazaki, Toru; Tateda, Kazuhiro (Frontiers in Cellular and Infection Microbiology, 2025)
Non-tuberculous mycobacteria infections, including Mycobacterium avium, are increasingly recognized as a growing public health concern, even among immunocompetent individuals. These infections are a significant cause of chronic pulmonary disease, and they are characterized by the formation of foamy macrophages (FMs) that facilitate bacterial persistence. Previously, we reported that apoptosis inhibitor of macrophage (AIM), a protein secreted by macrophages, promotes lipid droplet accumulation in M. avium-infected macrophages. However, the precise role of AIM in modulating immune responses remains unclear. This study aimed to elucidate the effect of AIM on FM formation, bacterial burden, and immune response in M. avium-infected mice by comparing AIM knockout (KO) mice with wild-type mice. Histological analysis revealed a reduction in FM formation in AIM KO mice, accompanied by decreased lipid droplet accumulation and altered expression of lipid metabolism-related genes. Furthermore, AIM KO mice exhibited a reduced bacterial load in the lungs, highlighting decreased cytokine production, including IL-1β, compared to wild-type mice. In addition, the analysis of the immune cells of AIM KO mice using flow cytometry revealed an increase in M1 macrophages and IFN-γ-producing T cells, as well as a decrease in M2 macrophages and interleukin 10 (IL-10)-producing T cells. The reduced expression of CD36 and PD-L1 in macrophages from AIM KO mice further supports the skewing toward an M1 phenotype. In vitro experiments with bone marrow-derived macrophages (BMDMs) confirmed reduced bacterial growth and lipid droplet formation in AIM KO BMDMs, which was restored by AIM and IL-10 treatment. These findings suggest that AIM contributes to the promotion of FM formation by establishing an immunosuppressive environment that promotes the establishment of M. avium through IL-10 production.